Association between circadian rhythm and sleep quality among nursing interns: A latent profile and moderation analysis - Wu, Xiaona; Lu, Yingzi; Xie, Xian; Chen, Rongjie; Zhang, Ningning; Zhou, Chen; Ye, Zengjie (Frontiers in Neuroscience, 2022)
Background Disturbances in circadian rhythms are common among night-shift workers and result in poor sleep quality. Nevertheless, the heterogeneity of circadian rhythms and their relationship with sleep quality is less explored in nursing interns. Therefore, we aimed to identify the latent subtypes of circadian rhythm, explore their relationship with sleep quality, and evaluate their moderating role between perceived stress and sleep quality in nursing interns. Materials and methods In all, 452 nursing interns were recruited between October 2020 and January 2021 from Be Resilient to Nursing Career (BRNC), which is a multicenter, prospective cohort of a career growth program for nursing students. They were assessed using the 10-item Chinese Perceived Stress Scale, Circadian Type Inventory, and Pittsburgh Sleep Quality Index. Latent profile analysis and moderation analysis were performed. Results Overall, 72.3% of the nursing interns reported poor sleep quality. We identified three latent subtypes of circadian rhythms, namely, Vigorousness (40.1%), Inadaptability (18.6%), and Flexibility (41.1%). Females (OR = 1.97, 95% Cl: 1.01–3.83, P = 0.047) with normal body mass index (OR = 1.62, 95% CI: 0.95–2.76, P = 0.078) were prone to Flexibility. Circadian rhythm types significantly moderated the association between perceived stress and sleep quality (P < 0.05). Conclusion Nursing interns suffer from poor sleep. There exists heterogeneity of circadian rhythm subtypes in nursing interns, and attention should be paid to those with Inadaptability type. The association between perceived stress and sleep quality is significantly moderated by circadian rhythm subtypes.